2019
DOI: 10.1111/cas.14156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor microenvironment on the efficacy of epidermal growth factor receptor‐tyrosine kinase inhibitors in patients with EGFR‐mutant non‐small cell lung cancer

Abstract: We retrospectively investigated the impact of the tumor microenvironment (TME) on the efficacy of epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitors (TKIs) as first‐line treatment in 70 patients with advanced EGFR‐mutant non‐small cell lung cancer and who were seen at Osaka City University Hospital (Osaka, Japan) between August 2013 and December 2017. Using immunohistochemical staining with 28‐8 and D7U8C Abs, the tumor proportion score was assessed for programmed cell death‐1 ligand‐1 (PD‐L1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…30,44 Recent studies suggest that TME interacts with EGFRmutant tumors, which affects the efficacy of TKI treatment as shown in the field of immunotherapy. 24,45 Matsumoto et al divided the TME into four types based on PD-L1 expression and CD8+ T cells, and demonstrated that PD-L1+/CD8+ tumors exhibited the lowest RR (14.3%) and the shortest median PFS (2.4 months), while PD-L1-/CD8+ patients showed best RR (78.6%) and the longest PFS (17.5 months) in EGFR-mutant patients treated with TKIs. 45 In addition, Yang et al evaluated the impact of various immune cells in TME including regulatory T cells and macrophages, and demonstrated the possible association between CD20+ B cell and tumor response in the same clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…30,44 Recent studies suggest that TME interacts with EGFRmutant tumors, which affects the efficacy of TKI treatment as shown in the field of immunotherapy. 24,45 Matsumoto et al divided the TME into four types based on PD-L1 expression and CD8+ T cells, and demonstrated that PD-L1+/CD8+ tumors exhibited the lowest RR (14.3%) and the shortest median PFS (2.4 months), while PD-L1-/CD8+ patients showed best RR (78.6%) and the longest PFS (17.5 months) in EGFR-mutant patients treated with TKIs. 45 In addition, Yang et al evaluated the impact of various immune cells in TME including regulatory T cells and macrophages, and demonstrated the possible association between CD20+ B cell and tumor response in the same clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…A shift in TAMs towards a phenotype promoting tumor growth was observed in gastro-intestinal stromal tumors (GISTs) becoming resistant to imatinib [64]. In addition, the RTKIs targeting EGFRs seem less effective in patients with a tumor highly infiltrated by CD8+ lymphocytes and associated with a high level of programmed death-ligand 1 (PD-L1) [75]. Taken together, these results indicate that an anti-tumor activity of immune TME seems important in the effectiveness of RTKIs [75].…”
Section: Impact Of the Immune Microenvironment On Receptor Tyrosine Kmentioning
confidence: 99%
“…In addition, the RTKIs targeting EGFRs seem less effective in patients with a tumor highly infiltrated by CD8+ lymphocytes and associated with a high level of programmed death-ligand 1 (PD-L1) [75]. Taken together, these results indicate that an anti-tumor activity of immune TME seems important in the effectiveness of RTKIs [75]. In addition, the immune cells of the microenvironment can act through other mechanisms than immunity.…”
Section: Impact Of the Immune Microenvironment On Receptor Tyrosine Kmentioning
confidence: 99%
“…Su et al have explored that dual positivity of PD-L1þ tumour cells and CD8þ T cells correlated with poor TKI responses [24]. Yoshiya et al further divided the tumour microenvironment of EGFR-mutated ADC into four types according to the PD-L1þ tumour cell and CD8þ T cell [50] and demonstrated the worst PFS in PD-L1 high/CD8 high patients. Moreover, patients with PD-L1 low/CD8 high had the longest PFS of EGFR TKI in his study, compared to PD-L1 high/CD8 low and PD-L1 low/CD8 low groups.…”
Section: Studymentioning
confidence: 99%